A patient‐specific approach to develop an exclusion diet to manage food allergy in infants and children. Issue 2 (30th January 2018) - Venter, C.; Groetch, M.; Netting, M.; Meyer, R.
Abstract: Food allergy is becoming increasingly common in infants and young children. This article set out to explain the different factors that should be taken into account during an individualized allergy consultation: Foods to avoid and degree of avoidance, suitable alternatives, self‐management skills, co‐ and cross‐reactive allergens and novel allergens alongside the role of the industry in allergen avoidance, importance of nutritional aspects of the diet and the future directions that nutritional guidance make take. Allergy management advice should be individualized to provide a patient‐specific approach. Changes in the management of food allergies have in particular occurred in nut, milk and egg allergies over the past few years. There has also been a progressive increase in our understanding of cross‐reactivity between different foods and also food and aero‐allergens. A patient‐specific approach of allergen avoidance should consider factors relating to industry and the environment such as food and nutrition literacy, threshold levels, cross‐contact/contamination and safe eating away from home. Increasing migration and travel has also led to exposure of unfamiliar foods. As understanding improves on individual allergens and threshold levels, food labels and food labelling laws are affected. Allergy specialist dietitians should also keep up to date with the latest information on nutrition, the gut microbiome and the immune system to incorporate nutrition strategies in a dietetic consultation using an evidence‐based approach.